Application of simulation to selecting project strategy for autonomous research projects at public universities - Dorota Kuchta; Stanisław Stanek (Administrative Sciences, 2020)
The definition of the success of research projects implemented at public universities is far from being unequivocal. The success of a research project has to be in line with both the public university's and the funding institution's policies, as well as with the personal objectives and ambitions of the researchers. Once the success definition for the research project has been determined, the strategy of implementation must be defined. The omission of this step may result in effort lost (public money, time, enthusiasm, etc.) after being directed toward objectives which do not fit with either the public university's or the funding agency's policies, nor with the researchers' personal objectives. This paper discusses this problem and proposes a model where simulation is used to choose the project strategy that best fits the selected research project success definition in the context of the policy of a given public university, the preferences of its researchers, and the policy of the funding agencies. The model is illustrated by means of a case study-a real world research project implemented at a public university in a European country, where the policy of subsidizing public universities has been changing both very regularly and in a highly unpredictable manner. It is shown how various project strategies can lead to multiple project outcomes, which are then evaluated in different ways depending on the point of view of public university policy or of the researchers, the funding agencies, and/or society. The main conclusion is that applying simulation to a research project before it starts may contribute significantly to the optimization of time, effort, and resource usage with the objective of project success maximization in the context of public university policy and the objectives of the researchers.
Keywords: 350; research project; project strategy; research project success; research project simulation; public university policy